SARS-CoV-2 spike HexaPro formulated in aluminium hydroxide and administered in an accelerated vaccination schedule partially protects Syrian Hamsters against viral challenge despite low neutralizing antibody responses - Christensen, Dennis; Polacek, Charlotta; Sheward, Daniel J.; Hanke, Leo; McInerney, Gerald; Murrell, Ben; Hartmann, Katrine Top; Jensen, Henrik Elvang; Zimmermann, Julie; Jungersen, Gregers; Illigen, Kristin Engelhart; Isling, Louise Krag; et al. (Frontiers in Immunology, 2023)
SARS-CoV-2 continues to pose a threat to human health as new variants emerge and thus a diverse vaccine pipeline is needed. We evaluated SARS-CoV-2 HexaPro spike protein formulated in Alhydrogel® (aluminium oxyhydroxide) in Syrian hamsters, using an accelerated two dose regimen (given 10 days apart) and a standard regimen (two doses given 21 days apart). Both regimens elicited spike- and RBD-specific IgG antibody responses of similar magnitude, but in vitro virus neutralization was low or undetectable. Despite this, the accelerated two dose regimen offered reduction in viral load and protected against lung pathology upon challenge with homologous SARS-CoV-2 virus (Wuhan-Hu-1). This highlights that vaccine-induced protection against SARS-CoV-2 disease can be obtained despite low neutralizing antibody levels and suggests that accelerated vaccine schedules may be used to confer rapid protection against SARS-CoV-2 disease.